Analysis of the Effectiveness of Policy Implementation Passenger Services - Cahyadie, Hendra; kasmad, Rulinawaty; Syamsuri, Syamsuri; Purwanto, Agus Joko (International Journal of Law Policy and Governance, 2024)
this research  uses a qualitative approach based on the Theory of Public Policy Implementation presented by George Edward III. According to Edward III, there are 4 (four) crucial variables in the implementation of public policy, namely: communication, resources, character or attitude and bureaucratic structure. And for this purpose, a policy model is needed to simplify understanding of the concept of policy implementation.  In this research the author decided to focus on the Communication and Resources variables. Communication was chosen in relation to the focus of this TAPM research on providing information to passengers through the availability of Electronic Notice Boards, while Resources were related to the provision of Trolleys to be used by Passengers. The results of the research show that based on Article 3 Paragraph (1) PM 38 of 2015 concerning Domestic Air Transport Passenger Service Standards, it is declared effective at the II Iskandar Pangkalan Bun Airport Management Unit both in terms of Trolley Availability and Electronic Notice Board Facilities